The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4049/jimmunol.1501531
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Airway Hyperresponsiveness in a Murine Model of Steroid-Resistant Airway Inflammation

Abstract: IL-13 and IL-17A, produced mainly by Th2 and Th17 cells respectively, have an influential role in asthma pathogenesis. We examined the role of IL-13 and IL-17A in mediating airway hyperresponsiveness (AHR), lung inflammation, and mucus metaplasia in a dual Th2/Th17 model of asthma. IL-13 and/or IL-17A were neutralized using monoclonal antibodies. Th2/Th17 adoptive transfer induced a mixed asthma phenotype characterized by elevated eosinophilia and neutrophilia, tissue inflammation, mucus metaplasia, and AHR th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…33 Further, co-transfer of T H 2 and T H 17 cells together induced steroid-resistant disease with mixed eosinophilic/neutrophilic inflammation, AHR and mucus hypersecretion. 34 These findings in mouse models demonstrate the key importance of T H cell polarization in regulating the type of inflammation in the lung, and provide evidence that T H 1/ T H 17-skewed responses can induce steroid-resistant inflammatory and pathogenic pathways. T cell polarization secondary to lung infection may also explain steroid resistance observed in infection-induced exacerbation models (described below).…”
Section: Steroid Resistancementioning
confidence: 66%
“…33 Further, co-transfer of T H 2 and T H 17 cells together induced steroid-resistant disease with mixed eosinophilic/neutrophilic inflammation, AHR and mucus hypersecretion. 34 These findings in mouse models demonstrate the key importance of T H cell polarization in regulating the type of inflammation in the lung, and provide evidence that T H 1/ T H 17-skewed responses can induce steroid-resistant inflammatory and pathogenic pathways. T cell polarization secondary to lung infection may also explain steroid resistance observed in infection-induced exacerbation models (described below).…”
Section: Steroid Resistancementioning
confidence: 66%
“…Manni ML, et al . found that in patients with neutrophil-dominant severe asthma, decreased FEV1 could be associated with both positive and negative changes in lung compliance, suggesting that there is a disconnect between airway inflammation, AHR, and lung compliance (50,51). Thus, lung stiffening may be mechanistically distinct from methacholine responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Naïve mouse T cells were isolated from the spleens of OTII mice using CD4 + CD62L + selection beads (Miltenyi) (18). Bone marrow dendritic cells from C57BL/6 or STAT1−/− mice were pulsed with heat-killed MRSA or vehicle for 24 hours.…”
Section: Methodsmentioning
confidence: 99%